KARAKTERISTIK DAN SIFAT FISIS FIBROUS MATERIAL BERBAHAN BAKU LIMBAH SERAT TEBU DENGAN BAHAN PENGIKAT AMILUM - Aisyah Putri Rezki; Agus Rino; Silvi Trisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing generation of agro-industrial waste, particularly sugarcane bagasse, has become an environmental concern while simultaneously providing opportunities for the development of environmentally friendly value-added materials. This study aims to analyze the pore structure characteristics and physical properties of fibrous materials produced from sugarcane bagasse fibers using starch as a natural binder, with the objective of evaluating their potential as sustainable sound-absorbing materials. An experimental method was employed using three different mass ratios of sugarcane fiber to starch, namely 1:10, 2:10, and 3:10. The microstructural characteristics of the materials were examined using Scanning Electron Microscopy (SEM) to observe surface morphology, pore diameter, pore spacing, and fiber diameter. The physical properties evaluated included moisture content, density, and airflow resistivity. The results revealed that the specimen with a fiber-to-starch ratio of 3:10 exhibited the best overall performance, with a moisture content of 68%, density of 0.2611 g/cm³, and an airflow resistivity of 484.1989 Pa·s/m². SEM observations indicated that the material was predominantly composed of closed pores, with an average pore diameter of 231.3 μm, an average pore spacing of 1109.88 μm, and an average fiber diameter of 318 μm. Increasing the proportion of sugarcane fibers produced a denser material, reduced moisture content, and enhanced airflow resistance, which are favorable characteristics for sound absorption. These findings demonstrate that fibrous material fabricated from sugarcane bagasse fibers with starch as a natural binder has considerable potential as an eco-friendly, low-cost, and sustainable alternative to conventional synthetic acoustic materials.